Metodología cooperativa “los más chiquitos” para la inducción a los educadores/as pedagógicos del centro de desarrollo infantil “tunshi san nicolás”, comunidad Tunshi San Nicolás, parroquia licto, cantón Riobamba, provincia Chimborazo. - Jessica Mariela, Salazar Rivera (2019)
The present project has as its theme the Cooperative Methodology “Los Chiquitos” for the induction of pedagogical educators of the Child Development Center “Tunshi San Nicolás”, Tunshi Community San Nicolás, Licto Parish, Riobamba City, Chimborazo Province, where noted that the hired educators do not have the proper training to work with children, because they are high school graduates and do not have a professional degree of technological level in initial education or related areas being a fault for the Children's Center due to lack of knowledge and appropriate methodology for adequate integral development in infants; This is how the following general objective was set to demonstrate how the Cooperative Methodology "Los más pequeños”" strengthens the induction of pedagogical educators. For the development of the research, a pre-experimental, documentary and field design was used, and it could be designated that it is an applied research using the scientific, analytical and inductive methods. The data collection was carried out by means of the observation technique and as an instrument the observation sheet used to three pedagogical educators of the Child Development Center, which is the entire population. The results obtained both before and after applying the observation form confirm that the cooperative methodology allowed the level of preparation of the educators to be more effective, in addition to relating to each other and establishing bonds of trust in their work environment. Therefore, it is recommended that the executing organizations make a correct induction to the educators before they begin their work, complying with the technical regulations of the Child Development Centers.